Parenting for Mother's Careers for Children during Covid-19 in Islamic Education - Nurina, Annisa Indah; Khamid, Abdul (CV. Creative Tugu Pena, 2021)
The article aimed to knowing the upbringing patterns by career mother on children in islamic education during COVID-19 pandemic in Tlompakan village, Tuntang, Semarang Regency in year of 2020 . The type of this study was qualitative research. The subject of this research were the career mothers. The data collected through observation, interview, and documentation. The result of the study shows that most of mothers who have had career in the Tlompakan village, Tuntang , Semarang Regency in year of 2020, during COVID-19 pandemic has characteristics: 1) Make a study schedule, 2) Communication, 3) Study from home, more islamic education, 4) Divide the role of parenting. Because of the importance of a mother's upbringing toward children in islamic education, they had involved and teaching islamic education to their children since from the womb. Keywords: Parenting for Careers, Parenting in Covid-19, Islamic Education in Covid-19 Pandemic